Membrane Protein Mobility and Orientation Preserved in Supported Bilayers Created Directly from Cell Plasma Membrane Blebs - Richards, Mark J (Langmuir : the ACS journal of surfaces and colloids, 2016)
Membrane protein interactions with lipids are crucial for their native biological behavior, yet traditional characterization methods are often carried out on purified protein in the absence of lipids. We present a simple method to transfer membrane proteins expressed in mammalian cells to an assay-friendly, cushioned, supported lipid bilayer platform using cell blebs as an intermediate. Cell blebs, expressing either GPI-linked yellow fluorescent proteins or neon-green fused transmembrane P2X2 receptors, were induced to rupture on glass surfaces using PEGylated lipid vesicles, which resulted in planar supported membranes with over 50% mobility for multipass transmembrane proteins and over 90% for GPI-linked proteins. Fluorescent proteins were tracked, and their diffusion in supported bilayers characterized, using single molecule tracking and moment scaling spectrum (MSS) analysis. Diffusion was characterized for individual proteins as either free or confined, revealing details of the local lipid membrane heterogeneity surrounding the protein. A particularly useful result of our bilayer formation process is the protein orientation in the supported planar bilayer. For both the GPI-linked and transmembrane proteins used here, an enzymatic assay revealed that protein orientation in the planar bilayer results in the extracellular domains facing toward the bulk, and that the dominant mode of bleb rupture is via the "parachute" mechanism. Mobility, orientation, and preservation of the native lipid environment of the proteins using cell blebs offers advantages over proteoliposome reconstitution or disrupted cell membrane preparations, which necessarily result in significant scrambling of protein orientation and typically immobilized membrane proteins in SLBs. The bleb-based bilayer platform presented here is an important step toward integrating membrane proteomic studies on chip, especially for future studies aimed at understanding fundamental effects of lipid interactions on protein activity and the roles of membrane proteins in disease pathways